ANALISIS PENGGUNAAN INFORMASI AKUNTANSI DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMBUAT SENDIRI FLA KUE SUSEN PADA DOLPHIN DONUTS BAKERY. - Muhamad, Intan Zuriati Agustina; Ilat, Ventje; Sabijono, Harijanto (Universitas Sam Ratulangi, 2013)
In runningÂ a business every company always faced with many issues. There are many kinds of issues, decison makingÂ was one of them. Many informations are needed for the management in order to chose the right decision. Differential accounting information was one of the information that the management need as basis of palnning and decisions making. Differential cost analysis was appropiate for the issue in ways for the company to increase the profit and reduce the loss,Â which to make the decision to make or buy the material. The purpose of this research is to find out what was the right decision that the manager could took, either to make or to buy the fla using differential accounting information with comparing the differential cost within to buy or to make the fla.The result of the analysist at Dolphin Donuts bakery from differential cost showing that differential accounting information in short-term decision indicating the company better make their own fla as the material of susen, cause the production cost was more cheaper comparing if the company buy from supplier.